2003
DOI: 10.1179/000349803225001373
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of treatment with intralesional meglumine antimoniate alone, compared with that of cryotherapy combined with the meglumine antimoniate or intralesional sodium stibogluconate, in the treatment of cutaneous leishmaniasis

Abstract: It would be very useful to have a more effective and more rapid method available for the treatment of cutaneous leishmaniasis (CL). The main aim of the present, Iranian study, was to see if the combination of cryotherapy and intralesional injections with meglumine antimoniate (C + MA) would be more effective than the injections given alone (MA) or the combination of cryotherapy plus intralesional sodium stibogluconate (C + SS). Forty patients (with 67 lesions) were treated with C + MA, another 40 (with 65 lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 16 publications
1
37
1
2
Order By: Relevance
“…1 In an attempt to improve upon this cure rate by increasing the number of ILSb injections, the present report first compared ILSb-3 injections versus ILSb-5 injections. In the Old World, another approach to improving the cure rate of ILSb is to combine ILSb with cryotherapy, [10][11][12][13] but with L. braziliensis in our hands, cryotherapy was both ineffective and poorly tolerated. 1 In Study 1 of the present report, the cure rate for ILSb-3 injections was 57% versus a cure rate for ILSb-5 injections of 73%.…”
Section: Discussionmentioning
confidence: 99%
“…1 In an attempt to improve upon this cure rate by increasing the number of ILSb injections, the present report first compared ILSb-3 injections versus ILSb-5 injections. In the Old World, another approach to improving the cure rate of ILSb is to combine ILSb with cryotherapy, [10][11][12][13] but with L. braziliensis in our hands, cryotherapy was both ineffective and poorly tolerated. 1 In Study 1 of the present report, the cure rate for ILSb-3 injections was 57% versus a cure rate for ILSb-5 injections of 73%.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Different methods were used, but one of the most commonly described methods was a two-cycle freeze and thaw using liquid nitrogen at weekly or fortnightly intervals. Usually, liquid nitrogen was applied to each lesion using a cotton-wool swab for 10 to 25 seconds and a 1-to 2-mm wide ring of the surrounding normal tissue appeared frozen.…”
Section: Cryotherapy Alone or In Combination With Other Treatmentsmentioning
confidence: 99%
“…For instance, around 90% healing rate from L. tropica infection in turkey was reported after one session of cryotherapy in combination with liquid nitrogen [72]. Another example for using of cryotherapy was reported in two studies in Iran, but this time in combination with local antimonials [73,74]. In the first study, high recovery rates from cutaneous leishmaniasis were reported with cryotherapy combined with intra-lesion antimonial, than antimonial by itself.…”
Section: And Vlmentioning
confidence: 87%